Variability in the fermentation index, polyphenols and amino acids of seeds of rambutan (Nephelium lappaceum L.) during fermentation - Shabnam, Mehdizadeh; Olusegun, Lasekan; Syed Muhammad, Sharifah Kharidah; Sham Baharin, Badlishah (Elsevier, 2015)
The variability in the fermentation index, polyphenols, and amino acids of rambutan seeds was investigated during fermentation. Results revealed that fermentation index (FI) value ≥1 was achieved on the 4th day of fermentation. While fermentation significantly reduced the levels of total polyphenols (59%), tannin (60%), and saponins (33%), it seems to have a moderate effect on geraniin, corilagin, and a much stronger effect on ellagic, and gallic acids. During fermentation, variability in gallic acid, geraniin, corilagin, and ellagic acid did not show a consistent trend. In contrast, amino acids significantly decreased up to the second day of fermentation. Importantly, amino acids (phenylalanine, tyrosine and leucine) with characteristic bitter taste showed reductions of 20%, 30%, and 40%, respectively after 10 days of fermentation. Sucrose, which was the only sugar present in significant concentrations in unfermented seed, was significantly reduced by fermentation.